TRANSFORMASIONAL LEADERSHIF DAN SERVANT LEADERSHIP: TANTANGAN KEPEMIMPINAN DALAM MENGHADAPI ERA GLOBAL - Jahidi, Idi; Hafid, Mochammad (CosmoGov, 2017)
The era of globalisation can allow for major changes in various aspects of human life, good political, economic, social, culture and others. So also the changes on the good institutions are engaged in the field of profit and on-profit organizations. This condition requires the leaders have adaptive leadership behavior and can anticipate various changes. Transformational leadership is seen as capable of transforming the visionary in the face of many changes so that the organization can realize the vision to become a reality. So also with the leadership of the ministry have credibility, integrity, patience, and spirit based on the ministry to contribute a catalyst for change in the achievement of the vision of the organization.